Penalaran Moral dan Perilaku Menyontek: Deskripsi Tingkatan serta Korelasinya pada Siswa - Friska Yuniar Nindi Pratiwi; Kusnarto Kurniawan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
Based on the preliminary study, it’s known that cheating behaviour is major problem for the education sector. The aim of this research is examine the correlation between moral reasoning and cheating behaviour of senior high school students. Current research is quantitative research with correlational method. 282 samples were selected using proportionate stratified random sampling technique. Moral reasoning variable were measured using psychological scale based on the level of moral reasoning according to Kohlberg’s theory and cheating behaviour variable were measured using psychological scale based on cheating behaviour indicators. Data were analysed using Product Moment correlation technique. After analysing the data, the results revealed there is significant negative relationship between moral reasoning and cheating behaviour (r=-.265, p.05) among senior high school students indicating when moral reasoning is high then cheating behaviour is low, and vice versa. It is expected that the continuation of this research can find interventions to reduce cheating behaviour.